Simulated Annealing 휴리스틱 기법을 이용한 임분탄소 최적화 프로그램의 개발 - 전어진(Eo-Jin Jeon); 김영환(Young-Hwan Kim); 박지훈(Ji-Hoon Park); 김만필(Man-Pil Kim) (韓國컴퓨터情報學會論文誌, 2013)
In this study, we developed a program of optimizing stand-level carbon stock using a stand-level yield model and the Simulated Annealing (SA) heuristic method to derive a optimized forest treatment solution. The SA is one of the heuristic algorithms that can provide a desirable management solution when dealing with various management purposes. The SA heuristic algorithm applied 'thermal equilibrium test', a thresholds approach to solve the phenomenon that does not find an optimum solution and stays at a local optimum value during the process. We conducted a sensitivity test for the temperature reduction rate, the major parameter of the thermal equilibrium test, to analyze its influence on the objective function value and the total iteration of the optimization process. Using the developed program, three scenarios were compared: a common treatment in forestry (baseline), the optimized solution of maximizing the amount of harvest(alternative 1), and the optimized solution of maximizing the amount of carbon stocks(alternative 2). As the results, we found that the alternative 1 showed provide acceptable solutions for the objectives. From the sensitivity test, we found that the objective function value and the total iteration of the process can be significantly influenced by the temperature reduction rate. The developed program will be practically used for optimizing stand-level carbon stock and developing optimized treatment solutions. 본 연구에서는 동적 임분 생장모델과 Simulated Annealing 휴리스틱 기법을 적용하여 최적의 산림시업체계를 도출하기 위한 임분탄소최적화 프로그램을 개발하였다. SA 휴리스틱 알고리즘은 다양한 경영목표를 다룰 때 비교적 짧은 시간 내에 만족할만한 수준의 경영안을 제공할 수 있는 최적화 기법으로서, 더 이상 최적해를 찾지 못하고 목표 값이 어떤 일정한 값(Local Optimum)에 계속 머무는 현상을 해결하기 위해 열균형 테스트를 이용하고 있다. 열균형 테스트에 적용되는 온도저감율 파라미터 값이 최적화 프로세스의 목적함수 값과 반복횟수에 미치는 영향을 분석하기 위해 본 연구에서는 온도저감율에 따른 민감도 분석을 실시하였다. 개발된 프로그램을 이용하여 기존의 산림경영에 주로 적용되고 있는 시업체계(베이스라인), 목재수확량 최대와 탄소저장량 최대의 3가지 산림시업 시나리오에 대해 비교 분석을 한 결과, 목재수확량 최대를 목표로 한 시나리오가 3개 시나리오 가운데 목재수확량이 가장 높은 것으로 나타났으며, 또한 탄소저장량을 최대로 하는 시나리오가 탄소저장량이 가장 높은 것으로 나타나, 본 연구에서 개발된 프로그램이 최적화된 결과를 도출하는 것으로 판단됐다. 온도저감율 파라미터 값에 대한 민감도 분석에서는 온도저감율에 따라 목적함수의 최적 값과 최적화 프로세스 반복횟수가 뚜렷한 영향을 받는 것으로 나타났다. 본 연구를 통해 개발된 임분탄소 최적화 프로그램은 앞으로 우리나라 산림의 탄소 최적화 시업체계 개발에 활용 될 것으로 기대된다.